Re-Imagining Wasatiyyah as a Socio-Theological Mediation of Youth Anger in Accra, Ghana - Prempeh, Charles (Unisia, 2022)
The paper recognizes that the current coronavirus has caused an anger spike that has brought in its wake global street demonstrations and protests against the ruling elite. In the case of Ghana, this has found expression in some of the young men and women of the country deploying their anger that brings them into conflict with the police – often leading to either death or destruction of property. Much as the issue of youth anger is transnational, in this article, the researcher focuses on two Muslim inner-cities in Accra, Nima, and Maamobi, to reflect on how wasatiyyah could be appropriated to mediate emerging religiopolitical tension in Ghana and the West African sub-region. It is instead for the sake of convenience of the researcher’s familiarity since, as a resident of a Muslim inner-city in Accra, the researcher seeks to destabilize the simplistic assertion that Islam is a violent religion, while Muslim youth in the urban slum is concomitantly incorrigibly aggressive. Thus, deploying autoethnography and ethnographic techniques of in-depth interviews, the article explores the intersections of Ghana's socio-political history and global and contemporary issues, including Covid-19 have spiked anger that needs critical reflection. The paper concludes that the anger in the Muslim communities in Accra is not isolated from the social history of Ghana and the global context. To keep the security of the country intact and offers the youth hope, wasatiyyah will help in explaining existential inequalities as well as reorienting people to deploy moral outrage productively.